Identification of P2X4 receptor-specific residues contributing to the ivermectin effects on channel deactivation - Jelínková, Irena; Yan, Zonghe; Liang, Zhaodong; Moonat, Sachin; Teisinger, Jan; Stojilkovic, Stanko S; Zemková, Hana (Biochemical and biophysical research communications, 2006)
Ivermectin (IVM) applied extracellularly increases the sensitivity of P2X4 receptor (P2X4R) to ATP, enhances the maximum current amplitudes, and greatly prolongs the deactivation kinetics. In this manuscript, we focused on identification of receptor-specific residues responsible for IVM effects on channel gating using the wild-type rat homomeric P2X4R, several chimeric P2X2/P2X4 receptors, and single-point P2X4R-specific mutants in the ectodomain and two transmembrane domains. Experiments with chimeric receptors revealed that the Val49-Val61 but not the Val64-Tyr315 ectodomain sequence is important for the effects of IVM on channel deactivation. Receptor-specific mutations placed in the Gly29-Val61 and Asp338-Leu358 regions showed the importance of Trp50, Val60, and Val357 residues in IVM regulation of the rate of channel deactivation, but not on the maximum current amplitude. These results suggest that the transmembrane domains and the nearby ectodomain region contribute to the effects of IVM on channel deactivation.
Keywords: tryptofan; adenosintrifosfát; antiparazitární látky; purinergní receptory P2; ivermektin; Valine; Sequence Homology, Amino Acid; vztah mezi dávkou a účinkem léčiva; molekulární sekvence - údaje; Amino Acid Sequence; Tryptophan; sekvenční homologie aminokyselin; Receptors, Purinergic P2; purinergní receptory P2X4; krysa rodu Rattus; Animals; lidé; Antiparasitic Agents; valin; Ivermectin; Receptors, Purinergic P2X4; Humans; zvířata; Rats; sekvence aminokyselin; Adenosine Triphosphate; Molecular Sequence Data; Dose-Response Relationship, Drug